An experimental method to identify neurogenic and myogenic active mechanical states of intestinal motility - Costa, Marcello; Wiklendt, Lukasz; Arkwright, John; Spencer, Nicholas; Omari, Taher; Brookes, Simon J H.; Dinning, Philip G. (Frontiers in Systems Neuroscience, 2013)
Excitatory and inhibitory enteric neural input to intestinal muscle acting on ongoing myogenic activity determines the rich repertoire of motor patterns involved in digestive function. The enteric neural activity cannot yet be established during movement of intact intestine in vivo or in vitro. We propose the hypothesis that is possible to deduce indirectly, but reliably, the state of activation of the enteric neural input to the muscle from measurements of the mechanical state of the intestinal muscle. The fundamental biomechanical model on which our hypothesis is based is the ‘three-element model’ proposed by Hill. Our strategy is based on simultaneous video recording of changes in diameters and intraluminal pressure with a fibre-optic manometry in isolated segments of rabbit colon. We created a composite spatiotemporal map (DPMap) from diameter (DMap) and pressure changes (PMaps). In this composite map rhythmic myogenic motor patterns can readily be distinguished from the distension induced neural peristaltic contractions. Plotting the diameter changes against corresponding pressure changes at each location of the segment, generates ‘orbits’ that represent the state of the muscle according to its ability to contract or relax actively or undergoing passive changes. With a software developed in MatLab, we identified twelve possible discrete mechanical states and plotted them showing where the intestine actively contracted and relaxed isometrically, auxotonically or isotonically, as well as where passive changes occurred or was quiescent. Clustering all discrete active contractions and relaxations states generated for the first time a spatio-temporal map of where enteric excitatory and inhibitory neural input to the muscle occurs during physiological movements. Recording internal diameter by an impedance probe proved equivalent to measuring external diameter, making possible to further develop similar strategy in vivo and humans.